2021
DOI: 10.1108/intr-07-2020-0368
|View full text |Cite
|
Sign up to set email alerts
|

Demographic factors have little effect on aesthetic perceptions of icons: a study of mobile game icons

Abstract: PurposeCustomization by segmenting within human–computer interaction is an emerging phenomenon. Appealing graphical elements that cater to user needs are considered progressively important, as the way a graphic is visually represented can greatly contribute to the interaction. However, aesthetic perceptions are subjective and may differ by target group. Understanding variations in user perceptions may aid in design processes; therefore, we set out to investigate the effects of demographic differences relating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The findings of this study can be utilized as the basis for redesigning icons, particularly for icons related to COVID-19 prevention measures [48]. Furthermore, the approach can also be applied and extended for evaluating other medical icons [49,50], safety icons, disaster-related prevention icons [51], transportation-related icons [52,53], and even entertainment-related icons [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study can be utilized as the basis for redesigning icons, particularly for icons related to COVID-19 prevention measures [48]. Furthermore, the approach can also be applied and extended for evaluating other medical icons [49,50], safety icons, disaster-related prevention icons [51], transportation-related icons [52,53], and even entertainment-related icons [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Literature [14] considers aesthetic elements as a kind of visual sign, and their study of architectural design in the Dutch East Indies found that aesthetic visual signs have a certain potential and hierarchical structure, which collectively contribute to the diversity of aesthetic elements of local public architectural design in the process of dynamic development of the place. Literature [15] identified HCI as an emerging aesthetic element that enhances users' aesthetic perceptions, and in their survey, HCI was found to be more important in the perception of aesthetic excellence among younger groups and women. Literature [16] evaluated visual aesthetics based on self-supervised feature learning; they designed two new interfaces to recognize the type and parameters of an image, built a layer of linear classifiers for evaluating the performance of binary aesthetic classification in an image, and conducted quantitative experiments on three benchmark datasets to extract the perceptual features of aesthetic elements of an image.…”
Section: Introductionmentioning
confidence: 99%
“…(Bloch, 1995). Several aspects of aesthetics such as works of art (Salkind & Salkind, 1997), moderns work of art (Silvia, 2005), shape of product design (Veryzer, 1993), perception of shape (Zhang, Feick, & Price, 2006), user experience (Sarsam & Al-Samarraie, 2018), and mobile game icons (Jylhä & Hamari, 2021) have been studied accordingly. Research on aesthetic perceptions toward demographic differences has been explored recently (Oyibo & Vassileva, 2018).…”
Section: Introductionmentioning
confidence: 99%